2017
DOI: 10.1111/liv.13355
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute‐on‐chronic liver failure on 90‐day mortality following a first liver transplantation

Abstract: LT is feasible in cirrhotic patients with ACLF. However, we have shown that ACLF is a significant and independent predictor of 90-day mortality. We propose a score that can identify candidate cirrhotic patients in whom LT might be associated with futile LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
153
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 39 publications
6
153
3
7
Order By: Relevance
“…CLIF‐SOFA (mean 10.3 vs. 4.3; P <.001) and MELD (mean 29.5 vs. 14.3; P <.001) scores at time of LT were significantly higher in ACLF patients compared with controls corresponding to significantly longer post‐LT ICU lengths of stay (17.5 vs. 11.5 days; P <.001). In contrast to previous studies, Levesque et al . demonstrated that ACLF patients had significantly decreased survival post‐LT at 90 days (79% vs. 96%) and 1 year (70% vs. 91%) compared with controls.…”
contrasting
confidence: 70%
See 2 more Smart Citations
“…CLIF‐SOFA (mean 10.3 vs. 4.3; P <.001) and MELD (mean 29.5 vs. 14.3; P <.001) scores at time of LT were significantly higher in ACLF patients compared with controls corresponding to significantly longer post‐LT ICU lengths of stay (17.5 vs. 11.5 days; P <.001). In contrast to previous studies, Levesque et al . demonstrated that ACLF patients had significantly decreased survival post‐LT at 90 days (79% vs. 96%) and 1 year (70% vs. 91%) compared with controls.…”
contrasting
confidence: 70%
“…Furthermore, comparing the number of organ failures, the present cohort may have had a higher burden on illness, hence contributing to poorer outcomes. In this cohort of ACLF Grade 3 patients going into LT, 33% had three organ failures and 66% had four or more organ failures whereas in CANONIC ACLF Grade 3 patients, 50% had three organ failures and 50% had four organ failures …”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The syndrome of ACLF is usually precipitated by an acute event, such as bacterial infection, which leads to organ failure(s) and subsequently ACLF . Outcomes of smaller cohorts or single‐center retrospective analyses of patients with ACLF who received a LT have shown that there is a decrement in overall survival after transplant in patients with ACLF before transplant . However, more in‐depth analyses have previously shown that less severe disease (as defined by EASL‐CLIF grade 1 and 2 ACLF) did not portend a worse prognosis after LT, but more severe disease (EASL‐CLIF grade 3 ACLF) did .…”
Section: Discussionmentioning
confidence: 99%
“…Not only was post‐LT mortality affected by ACLF, but intensive care unit (ICU) length of stay and total hospital length of stay were longer in patients with versus without ACLF and rose with worsening grades of ACLF . It is important to highlight that the vast majority of studies either eliminated simultaneous liver‐kidney transplantation (SLKT) recipients or showed inferior outcomes among them when transplant occurred after ACLF …”
mentioning
confidence: 99%